Schoolʼs Holiday as Means of Upbringing of Pupils in the Secondary School of Ukraine (Second Half of XIX Century – 20th of XX Century): Historiography and Sources of Research - Valentyna Oliynyk (Pedagogical Discourse, 2013)
The article analyzes the scientific historiography and sources of research problem – school holiday as a means of educating students in a secondary school in Ukraine the second half of the nineteenth century – 20 years of the twentieth century. The source base of the  research is characterized by the involvement of a large number of sources of different origin.